Youth Awareness and Engagement in Promoting Yangon as Tourism Destination - Atar Thaung Htet (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Purpose – The role of youth is becoming important in promoting tourism destination. The major aim of this study is to assess the role of youth for promoting Yangon as tourism destination. There are two specific objectives for this study- 1) To assess the knowledge, attitude and behavior of youth for promoting the Yangon as tourism destination and 2)To examine the relationship of youth knowledge, attitude and behavior for promoting the Yangon as tourism destination. Methodology/approach – This study adopted the knowledge-attitude-behavior (KBA) model to assess the youth perception. The 133 students who currently studying the undergraduate program of private collages in Myanmar participated as major respondents in this study. The systematic sampling method was applied in this study. The reliability analysis, composite reliability , factors loading techniques applied to assess the youth knowledge, attitude and behavior for promoting the Yangon as tourism destination. The Pearson correlation analysis used as the hypothesis testing tools in this study. Findings – The findings of this study reveal the acceptance of proposed research hypotheses. There is positively relationship between knowledge, attitude and behavior of Youth for promoting Yangon as tourism destination. Novelty/value – This study recommends the integration of social media usage how applied in destination promotion and how design effective policy framework for promotion the Yangon as tourism destination.